PTH-028 A preliminary report on the feasibility and efficacy of the novel eus guided shark core fine needle biopsy. (17th June 2017) - Kasi, M; Fernandez-Sordo, J Ortiz; Kaye, P; Ragunath, K; James, M; Aithal, GP; Venkatachalapathy, SV
Abstract : Introduction: EUS guided Fine Needle aspiration (FNA) is the standard of care for diagnosing solid pancreatic lesions. However, with personalised approach to oncological treatment histology is required to improve diagnostic accuracy and molecular characterisation. In a recent meta-analysis, the pooled sensitivity and specificity for EUS Fine Needle Biopsy (FNB) needle for diagnosing solid tumours is 84% and 99% respectively (1) . A novel FNB needle has been introduced which has two sharp points of different lengths and it has a multifaceted bevel to capture additional tissue - Shark Core (SC). There has been limited data on this needle type. Our aim was to study the feasibility and efficacy of FNB-SC for diagnosing solid pancreatic and non-pancreatic lesions. Method: We conducted a retrospective cohort study in which, all consecutive patients who had FNB-SC for solid tumours between July 2016 and January 2017, were identified through endoscopy database. The endoscopy reports, histology reports and Hepato-Pancreato-Biliary MDM outcomes were reviewed through hospital reporting systems. The histopathologist reviewed the tissue adequacy on all samples. We assessed the histological yield and diagnostic accuracy of the FNB-SC needle. Results: 29 patients were included in study of which, 55% (n=16) males and 45% (n=13) females with median age of 65 years (range 33–84). 26 patients (86%) had pancreatic lesions and 3 were non pancreatic lesions (2 GIST, 1 Ampullary adenoma). Median size of the lesions was 30 mm (range 17 mm-70mm). Sample deemed adequate for histological analysis in 96.5% (n=28) and inadequate in 3.5% (n=1). 22gauge needle was used in 86% and 25gauge in 14% of the patients. The Median number of passes to obtain adequate sample are 3 (range 2–4). Among the adequate samples obtained histological diagnosis were matched with radiological diagnosis in 89.2% (25/28) and with clinical diagnosis in 83% (24/28) at three months follow up with no further cancer detected. There was only one patient who had surgery in whom the histology results from surgical specimen matched with FNB diagnosis. The sensitivity, specificity, positive predictive value and negative predictive value for diagnostic accuracy were 92.8% (95% CI 76.5%>99.1%), 100% (95% CI 2.5%>100%), 100%, 33.3% (95% CI 11.6%–65.5%) respectively. There were no complications in our cohort of patients. Conclusion: EUS FNB-SC needle is feasible and effective in obtaining tissue for solid tumours. It has high sensitivity and specificity in diagnosing solid tumours. Reference: . Yang, Yongtao, et al. "Endoscopic ultrasound-guided fine needle core biopsy for the diagnosis of pancreatic malignant lesions: a systematic review and Meta-Analysis."Scientific reports6 (2016). Disclosure of Interest: None Declared